Characterization of a Microalgal UV Mutant for CO2 Biofixation and Biomass Production. (23rd December 2018) - Qi, Feng; Wu, Daoji; Mu, Ruimin; Zhang, Shuo; Xu, Xinyi
Abstract : The mutagenesis is an emerging strategy for screening microalgal candidates for CO2 biofixation and biomass production. In this study, by 96-well microplates-UV mutagenesis, a mutant stemmed from Scenedesmus obliquus was screened and named as SDEC-1M. To characterize SDEC-1M, it was cultivated under air and high level CO2 (15% v/v), and its parental strain (PS) was considered as control. Growth characterizations showed that SDEC-1M grew best in high level CO2 . It indicated that the mutant had high CO2 tolerance (HCT) and growth potential under high level CO2 . Richer total carbohydrate content (37.26%) and lipid content (24.80%) demonstrated that, compared to its parental strain, SDEC-1M was apt to synthesize energy storage materials, especially under high CO2 level. Meanwhile, the highest light conversion efficiency (approximately 18 %) was also obtained. Thus, the highest overall biomass productivities were achieved in SDEC-1M under high level CO2, largely attributed to that the highest productivities of total lipid, total carbohydrate, and crude protein were also achieved in the meantime. By modified UV, therefore, mutagenized SDEC-1M was the better candidate for CO2 biofixation and biofuel production than its parental strain.